Magnesium doped calcium phosphate sodium alginate biocomposite for bone implant application - Mustaffa, Nor Azimah (2018)
Calcium phosphate (CaP) usually been used for bone implant application due to the similarity mineral in natural bone and it is bioactive and biocompatible material. However, CaP has low mechanical strength under load bearing condition and limited on certain application only. Therefore, sodium alginate (SA), a natural polymer is combined with CaP and doped with magnesium (Mg) to improve the properties of the CaP. CaP/SA biocomposite was successfully prepared by using precipitation method with different ratio of CaP/SA (100/0, 99/1, 97/3, 95/5, 90/10, and 80/20). 95/5 ratio of CaP/SA which the optimum properties of density, hardness, and microstructure analysis was selected to doped with Mg. The composite was then doped with different weight percentage of Mg (0 wt%, 1.0 wt%, 1.5 wt%, and 2.0 wt%) by using similar method. From FTIR analysis, the addition of Mg in CaP was observed decreasing the phosphate group intensity due to substitution of Mg in CaP that also supported in XRD analysis where new phase was formed in Mg doping that belongs to Mg-whitlockite (Ca2.71Mg0.29(PO4)2. Furthermore, the addition of SA and Mg was confirmed by EDS analysis where the mass percentage of these elements were increased as increasing the SA and Mg content. Microstructure from SEM has shown formation small and large grain with average grain size obtained 2.61 μm which leds to the strong bonding resulted maximum hardness at 5.34GPa after doped with 1.5wt%. The density also improved at similar weight percentage with 2.92g/cm3. From the result, 1.5wt% Mg that has been doped with 95/5 CaP/SA was showed the best combination based on physical and mechanical properties.